What the Transformation of Telecom Markets Means for Regulation - Smith, Peter (World Bank, Washington, DC, 2012)
The author looks at the impact of the changes in the telecommunications industry on regulation. As demand changes, services converge, and new players emerge, the key issue for regulators is promoting competition. The work of regulators is becoming increasingly complex at the same time that convergence and the common principles established in regional and international trade agreements are reducing their discretion. One way for regulators to deal with the complexity is to privatize aspects of regulation-for example, by creating property rights to the spectrum and by outsourcing some regulatory tasks. But the specialized telecommunications regulatory agency is probably a transitory entity that may eventually find itself merged into a multisectoral antitrust agency.